Burn depth assessment using hyperspectral imaging in a prospective single center study. Issue 5 (August 2022) - Schulz, Torsten; Marotz, Jörg; Seider, Sebastian; Langer, Stefan; Leuschner, Sebastian; Siemers, Frank
Highlights: Hyperspectral imaging provides accurate information about burn wounds. Mixed partial thickness burns are characterized by the Burn Index. The Burn Index demonstrates an accuracy of 92% on the third day after trauma. Surgical approach is recommended, if the Burn Index is ≤1.27 after 72 h. ABSTRACT: Background: The assessment of thermal burn depth remains challenging. Over the last decades, several optical systems were developed to determine burn depth. So far, only laser doppler imaging (LDI) has been shown to be reliable while others such as infrared thermography or spectrophotometric intracutaneous analysis have been less accurate. The aim of our study is to evaluate hyperspectral imaging (HSI) as a new optical device. Methods: Patients suffering thermal trauma treated in a burn unit in Germany between November 2019 and September 2020 were included. Inclusion criteria were age ≥18 years, 2 nd or 3 rd degree thermal burns, written informed consent and presentation within 24 h after injury. Clinical assessment and hyperspectral imaging were performed 24, 48 and 72 h after the injury. Patients in whom secondary wound closure was complete within 21 days (group A) were compared to patients in whom secondary wound closure took more than 21 days or where skin grafting was indicated (group B). Demographic data and the primary parameters generated by HSI were documented. A Mann Whitney-U test was performed to compare the groups. A p-value below 0.05 was considered to be statistically significant. The data generated using HSI were combined to create the HSI burn index (BI). Using a logistic regression and receiver operating characteristics curve (ROC) sensitivity and specificity of the BI were calculated. The trial was officially registered on DRKS (registration number: DRKS00022843). Results: Overall, 59 patients with burn wounds were eligible for inclusion. Ten patients were excluded because of a poor data quality. Group A comprised 36 patients with a mean age of 41.5 years and a mean burnt body surface area of 2.7%. In comparison, 13 patients were allocated to group B because of the need for a skin graft (n = 10) or protracted secondary wound closure lasting more than 21 days. The mean age of these patients was 46.8 years. They had a mean affected body surface area of 4.0%. 24, 48, and 72 h after trauma the BI was 1.0 ± 0.28, 1.2 ± 0.29 and 1.55 ± 0.27 in group A and 0.78 ± 0.14, 1.05 ± 0.23 and 1.23 ± 0.27 in group B. At every time point significant differences were demonstrated between the groups. At 24 h, ROC analysis demonstrated BI threshold of 0.95 (sensitivity 0.61/specificity 1.0), on the second day of 1.17 (sensitivity 0.51/specificity 0.81) and on the third day of 1.27 (sensitivity 0.92/specificity 0.71). Conclusion: Changes in microcirculation within the first 72 h after thermal trauma were reflected by an increasing BI in both groups. After 72 h, the BI is able to predict the need for a skin graft with a sensitivity of 92% and a specificity of 71%.